Pengaruh Kualitas Produk, Pelayanan, dan Emosional Terhadap Kepuasan Orang Tua di Sekolah Dasar Swasta Unggulan - Amalia, Resa; Imron, Imron (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study was to determine the influence of product quality, service, and emotional factors on parental satisfaction at a leading private elementary school in Mertoyudan District. This study is a quantitative study. The population in this study were all guardians of students from Al Firdaus Islamic Elementary School and Muhammadiyah Inovatif Elementary School totaling 837 people. The sampling technique in this study used simple random sampling. Data analysis in this study used descriptive statistical analysis and multiple linear regression. From this study, the first result was obtained, product quality influenced parental satisfaction with a significance of 0.030 0.05. Second, service quality influenced parental satisfaction with a significance of 0.001 0.05. Third, emotional factors influenced parental satisfaction with a significance of 0.000 0.05. Fourth, product quality, service, and emotional factors together influenced parental satisfaction with a significance of 0.000 0.05. Furthermore, it is known that the coefficient of determination of the influence of product quality, service, and emotional factors on parental satisfaction at the Leading Private Elementary School in Mertoyudan District is 93.1%, while the remaining 6.1% is influenced by other factors that were not studied. Therefore, educational institutions must be able to maximize these three factors. Good product and service quality will form positive emotions from parents which will later lead to parental satisfaction.